PEMODELAN PENGUJIAN TARIK UNTUK MENGANALISIS SIFAT MEKANIK MATERIAL - Robert Denti Salindeho; Jan Soukotta; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
One of the tests used to determine the mechanical properties of the metal are tensile test. The results obtained from tensile testing is the yield strength of the material. In the tensile test, applying load and extension of the material are manually analyzed. The research objective is to develop software and perform simulation of tensile testing test based on applying load and extension. Simulation results can determine the of technical strength and true strength of material the base on the results of tensile testing specimens of copper shafts circular cross section and angle shape cross section of construction steel specimen. Keywords: Software Modeling, Testing Test, Strength of Â Materials